2022
DOI: 10.3390/ijms232214193
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Acute Kidney Injury in COVID-19: Possible Mechanisms and Future Perspectives

Abstract: Since the outbreak of COVID-19 disease, a bidirectional interaction between kidney disease and the progression of COVID-19 has been demonstrated. Kidney disease is an independent risk factor for mortality of patients with COVID-19 as well as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection leading to the development of acute kidney injury (AKI) and chronic kidney disease (CKD) in patients with COVID-19. However, the detection of kidney damage in patients with COVID-19 may not occur until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 128 publications
1
4
0
Order By: Relevance
“…In contrast, biomarkers of kidney damage, particularly NGAL, more clearly signified renal aggression, whatever the cause, likely to lead to AKI, and consequently its performance in predicting such cases was better. Thus, our results and those of others [ 12 , 37 , 40 , 41 ] suggest to use urinary biomarkers to better define renal involvement in COVID-19, reflecting the heterogeneity in the clinical presentation and severity and including subclinical AKI which concerned almost 20% of our cohort.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In contrast, biomarkers of kidney damage, particularly NGAL, more clearly signified renal aggression, whatever the cause, likely to lead to AKI, and consequently its performance in predicting such cases was better. Thus, our results and those of others [ 12 , 37 , 40 , 41 ] suggest to use urinary biomarkers to better define renal involvement in COVID-19, reflecting the heterogeneity in the clinical presentation and severity and including subclinical AKI which concerned almost 20% of our cohort.…”
Section: Discussionsupporting
confidence: 67%
“…Our observations corroborate the existence of a continuum in the spectrum of COVID-19 associated AKI [ 4 , 24 , 39 ]. Indeed, some patients may present only subclinical AKI syndrome characterized by significant tubule injury (particularly, changes in the protein endocytosis machinery in proximal tubule epithelial cells) without changes in the glomerular filtration rate [ 12 , 37 , 40 , 41 ] while others may exhibit AKI related to various mechanisms [ 4 , 24 , 39 ]. This approach may explain why we found that proximal tubular dysfunction was a sensitive marker for detecting persistent AKI, but its specificity was relatively low and, conversely, it appeared less sensitive for identifying transient AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Subclinical AKI, defined as the presence of kidney dysfunction not meeting the criteria for AKI, has been described in SARS-CoV-2 infection. Even if clinical data are still poorly known, especially in MIS-C, it seems to be correlated to a more severe course of the disease ( 18 ). Our patient experienced a subclinical AKI by presenting, at admission, serum creatinine values that were double those when discharged.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in those patients requiring ICU support, AKI is associated with poor prognosis and increased risk of mortality. As a result of the studies mentioned above, we have observed that many laboratory parameters are useful as potential biomarkers to predict renal damage associated with COVID-19 [ 15 , 17 , 21 , 22 , 23 , 24 , 27 , 30 , 48 , 49 , 50 ].…”
Section: Methods: Identification and Characteristics Of Included Studiesmentioning
confidence: 99%